HAK ASUH ANAK (HADHANAH) ADOPSI PASCA PERCERAIAN MENURUT HUKUM ISLAM INDONESIA - Renata Thalyssa Kiara; Khairani Bakri (Reformasi Hukum Trisakti, 2022)
The institution of marriage serves to formalize a man and woman's connection and to create an everlasting and happy family. Child custody is one of the effects of divorce (hadhanah). Problem statement: Under Indonesian Islamic family law, how is child custody (hadhanah) for adopted children determined? And does Indonesian Islamic family law apply to the Sarolangun Religious Court's Decision Number 144/Pdt.G/2019/PA.Srl? The normative legal research type is utilized in this scientific work's study methodology. The research's descriptive nature, utilization of secondary data backed by primary data, qualitative analysis of the data, and deductive reasoning are all used to make findings. Research findings, analysis, and conclusions (Hanah) Arrangements for child custody for adoptive children have not been governed by Indonesian Islamic family law. The verdicts numbers three and four are not in conformity with the normative law contained in the KHI, as per the provisions of Article 105 letters a and b KHI. To ensure the child's welfare and that their rights are upheld, consideration is given to the child's actual living circumstances when deciding who will be responsible for caring for them.